1954
DOI: 10.1146/annurev.mi.08.100154.002313
|View full text |Cite
|
Sign up to set email alerts
|

Foods and Feeds from Fungi

Abstract: Current interest in the synthesis of food by microorganisms arises from three main considerations: (a) the critical need for food, and in particular for protein, that exists in many parts of the world; (b) the economic advantages of microbial elaboration of foods or vitamins from relatively inexpensive raw materials; (c) the reduction of the cost of disposal of fermentable factory wastes.The reader is asked to accept for the present purpose an interpretation of the titular word "fungi" to include mycelial form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0
3

Year Published

1955
1955
1999
1999

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 55 publications
1
4
0
3
Order By: Relevance
“…Our preliminary results indicated that, while these fungi probably did not contain a toxic principle, the mycelium was not nutritionally adequate as a sole source of food. Similar results have been observed with other kinds of fungi which have been assessed for nutritional value (see Thatcher, 1954).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Our preliminary results indicated that, while these fungi probably did not contain a toxic principle, the mycelium was not nutritionally adequate as a sole source of food. Similar results have been observed with other kinds of fungi which have been assessed for nutritional value (see Thatcher, 1954).…”
Section: Discussionsupporting
confidence: 88%
“…Submerged-culture mycelium of another mushroom-the edible morel, Morchella hortensis (an Ascomycete)-has been shown in our laboratory (Koda, 1951) to contain the same amino acids as does P. palustris, although in different proportions. References to other papers on various chemical constituents of higher fungi, including woodrotting Basidiomycetes, are given by Ralph (1949); the on September 3, 2020 by guest http://aem.asm.org/ Downloaded from distribution of vitamins in microorganiisms is reviewed by Van Lanen and Tanier (1948) and by Thatcher (1954).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Submerged-culture mycelium of another mushroom-the edible morel, Morchella hortensis (an Ascomycete)-has been shown in our laboratory (Koda, 1951) to contain the same amino acids as does P. palustris, although in different proportions. References to other papers on various chemical constituents of higher fungi, including woodrotting Basidiomycetes, are given by Ralph (1949); the on December 13, 2020 by guest http://aem.asm.org/ Downloaded from distribution of vitamins in microorganiisms is reviewed by Van Lanen and Tanier (1948) and by Thatcher (1954).…”
Section: Discussionmentioning
confidence: 99%